Mach das Beste aus Deiner To-do-Liste (Assemble You, 2022)
Welcome to our Assemble You Learning Podcast A well-organized to-do list means the tasks with the greatest impact need to be done first. So nothing is overlooked and at the end of the day you have a feeling that your duty has been fulfilled. As humans, we need a good to-do list above all because our brain is a very poor filing cabinet. We have a million things on our minds and nearly as many emotions to process. You can't rely on your brain to remember the hundreds of administrative tasks you need to do every day. For this you need a to-do list. In this course you will learn what a good to-do list looks like and how to prioritize and separate your tasks and projects. Then we look at planning your to-do list and which tools are most suitable for it. Learning Objectives Learn to manage and prioritize your time even more efficiently by using a to-do list in the right way.